Applications of the marketing mix in the operations of three selected kiosks in the Polytechnic Kota Kinabalu / Marielan Michael - Michael, Marielan (2015)
Public higher education in Malaysia comprise of public universities and polytechnics. Throughout Malaysia there are 32 polytechnics. In the state of Sabah there are 2 polytechnics which are in Kota Kinabalu and Sandakan. This study is focus on the Polytechnic Kota Kinabalu. In Polytechnic Kota Kinabalu, there is a unit called the Entrepreneurship Unit which functions as the motivator for the students to learn and be exposed in entrepreneurship. The Entrepreneurship Unit is responsible for the incubator program. There are three incubators that are run by this Unit namely Car Wash, Mini Mart and Saloon. Each premise is run by the students of Polytechnic Kota Kinabalu themselves, but still under the supervision of the Head of the Unit. This study is aim to help the Mini Mart incubator which is the latest kiosk in Polytechnic Kota Kinabalu to be operated in the cafeteria building of the Polytechnic. The cafeteria which consists of 6 kiosks is run by students, outsiders or graduates of Polytechnic Kota Kinabalu. The potential market for these kiosks is approximately more than 1000 customers per week including the students and the staff. Based on this population it is an opportunity for the Mini Mart incubator to gain profit. However, the biggest competitor for the Mini Mart is the Cooperative Shop of Polytechnic Kota Kinabalu.